Need Assessment for Undergraduate Medical Curriculum of Bangladesh Through Exploring The Views of Government Primary Health Care Doctors (Bangladesh Journal of Anatomy, 2010)
Objective: To identify the relevancy of contents of undergraduate medical curriculum of Bangladesh for providing service at primary health care (PHC) level through exploring the views of government PHC doctors. Methods: This descriptive study was conducted upon the government doctors who were working at primary health care level of Bangladesh. A total of 545 doctors of 176 upozilas of 62 districts of the country participated in this study by filling mailed self administered semi-structured questionnaires Result: It was found that majority of doctors were satisfied on their skill and knowledge that they acquired at undergraduate level. Their opinions indicated that clinical subjects of MBBS course need more emphasis than basic subjects. On the basis of their opinion a total of 129 health problems are prioritized according to the load of the health problems at the working place of PHC doctors. Conclusion: Curriculum of undergraduate medical education should be reviewed and more emphasis should be given on skills especially on the clinical subjects keeping in mind common health problem of Bangladesh Key words: Need Assessment Medical Curriculum; Medical Education Bangladesh; Undergraduate Curriculum Bangladesh; Health Needs Bangladesh; Curriculum Development Bangladesh.